Ghrelin prevents tumour‐ and cisplatin‐induced muscle wasting: characterization of multiple mechanisms involved. Issue 2 (22nd April 2015) - Chen, Ji‐an; Splenser, Andres; Guillory, Bobby; Luo, Jiaohua; Mendiratta, Meenal; Belinova, Blaga; Halder, Tripti; Zhang, Guohua; Li, Yi‐Ping; Garcia, Jose M.
Abstract: Background: Cachexia and muscle atrophy are common consequences of cancer and chemotherapy administration. The novel hormone ghrelin has been proposed as a treatment for this condition. Increases in food intake and direct effects on muscle proteolysis and protein synthesis are likely to mediate these effects, but the pathways leading to these events are not well understood. Methods: We characterized molecular pathways involved in muscle atrophy induced by Lewis lung carcinoma (LLC) tumour implantation in c57/bl6 adult male mice and by administration of the chemotherapeutic agent cisplatin in mice and in C2C12 myotubes. The effects of exogenous ghrelin administration and its mechanisms of action were examined in these settings. Results: Tumour implantation and cisplatin induced muscle atrophy by activating pro‐inflammatory cytokines, p38‐C/EBP‐β, and myostatin, and by down‐regulating Akt, myoD, and myogenin, leading to activation of ubiquitin‐proteasome‐mediated proteolysis and muscle weakness. Tumour implantation also increased mortality. In vitro, cisplatin up‐regulated myostatin and atrogin‐1 by activating C/EBP‐β and FoxO1/3. Ghrelin prevented these changes in vivo and in vitro, significantly increasing muscle mass ( P < 0.05 for LLC and P < 0.01 for cisplatin models) and grip strength ( P = 0.038 for LLC and P = 0.001 for cisplatin models) and improving survival ( P = 0.021 for LLC model). Conclusion: Ghrelin prevents muscle atrophy by down‐regulating inflammation, p38/C/EBP‐β/myostatin, and activating Akt, myogenin, and myoD. These changes appear, at least in part, to target muscle cells directly. Ghrelin administration in this setting is associated with improved muscle strength and survival.